DEMOCRATIC PUBLIC REASON AND RELIGIOUS PUBLIC REASONS (Revista Kriterion, 2021)
According to the democratic interpretation of public reason, political justification ought to appeal to the tacit dimension or common sense of society’s actual historical moment. This article claims that a consequence of this interpretation is that religious reasons can be stable public reasons. More specifically, it claims that religious reasons can be public reasons in pervasively religious communities that are democratic, even in circumstances of ongoing social secularization. Three theoretical consequences are derived from this claim: first, democratic public reason assumes more social integration than other interpretations of public reason; second, religious reasons are not always inaccessible to non-believers; and third, religious reasons, when public reasons, can have normative force upon non-believers. Additionally, the following practical implication is made explicit: while justification of state power can appeal to religious reasons only, the law cannot be written in religious terms.